Synthesis and inhibition of mushroom tyrosinase by new halogenated benzophenone and xanthone analogues: Toxicity assessment and molecular insights - Baharuddin, Fatin Farhana; Mad Nasir, Nadiah; Koh, Soo Peng; Adam, Zainah; Ismail, Ahmad Zaidi; Devakrishnan, Pavithren (Elsevier B.V., 2025)
A series of benzophenone and xanthone halogenated analogues were synthesized using a one-step reaction method and characterized via NMR, FTIR, and GC-MS. Their inhibitory effects on mushroom tyrosinase, a key enzyme in melanin biosynthesis, were evaluated. Among these analogues, three new compounds (3), (4), and (5) exhibited potent tyrosinase inhibition, with compound (4) demonstrating the highest efficacy of tyrosinase activity. It showed IC50 values of 9.0 and 118 µg/mL against L-tyrosine and L-DOPA substrates, respectively. Enzyme kinetic analysis revealed that compound (4) acts as a mixed inhibitor, effectively reducing melanin formation. Additionally, molecular docking analysis (PDB: 2Y9X) confirmed strong binding interactions between compound (4) and the mushroom tyrosinase protein. Crystal structure analysis indicated that this compound crystallizes in the monoclinic system with a P21/c space group. Toxicity assessments, including brine shrimp lethality, normal skin HaCaT cell viability, and in vivo zebrafish embryo toxicity assays, confirmed its non-toxic nature. These findings highlight compound (4) as a promising, non-toxic skin-whitening agent with potential applications in treating hyperpigmentation.